2018
DOI: 10.3389/fmicb.2018.03017
|View full text |Cite
|
Sign up to set email alerts
|

The Equine Gastrointestinal Microbiome: Impacts of Age and Obesity

Abstract: Gastrointestinal microbial communities are increasingly being implicated in host susceptibilities to nutritional/metabolic diseases; such conditions are more prevalent in obese and/or older horses. This controlled study evaluated associations between host-phenotype and the fecal microbiome / metabolome. Thirty-five, Welsh Mountain pony mares were studied across 2 years (Controls, n = 6/year, 5–15 years, Body Condition Score (BCS) 4.5–6/9; Obese, n = 6/year, 5–15 years, BCS > 7/9; Aged, n = 6 Year 1; n = 5 Year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
94
4
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(112 citation statements)
references
References 63 publications
(86 reference statements)
13
94
4
1
Order By: Relevance
“…The predominant phyla identified in the fecal microbiome of healthy horses of the current study included Bacteroides and Firmicutes, similar to previous observations by Costa [39] and Morrison; [13] in addition to Verrucomicrobia (see Fig 2). In contrast, a relatively low abundance of Verrucomicrobia was noted in diarrheic horses, with an inverse correlation between diarrhea score and relative Verrucomicrobia abundance.…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…The predominant phyla identified in the fecal microbiome of healthy horses of the current study included Bacteroides and Firmicutes, similar to previous observations by Costa [39] and Morrison; [13] in addition to Verrucomicrobia (see Fig 2). In contrast, a relatively low abundance of Verrucomicrobia was noted in diarrheic horses, with an inverse correlation between diarrhea score and relative Verrucomicrobia abundance.…”
Section: Plos Onesupporting
confidence: 90%
“…Geriatric age of donor horses (� 20 years old) did not significantly affect the equine fecal microbiome in the population of healthy horses screened in this study. In contrast, previous reports have documented inconsistent effects of advancing age on the equine intestinal microbiome, with both inverse [14] and direct relationships [13] being observed between aging and fecal microbial diversity. The current study suggests that age-matching between donor and FMT recipients is not required to optimize microbial transplantation in adult horses.…”
Section: Plos Onecontrasting
confidence: 62%
See 1 more Smart Citation
“…But other authors working with a different mouse strain showed lower caecal concentrations of SCFA in obese mice [25]. In horses no differences in the faecal SCFA concentrations of different weight groups have been demonstrated [9,26].…”
Section: Plos Onementioning
confidence: 85%
“…As hindgut fermenters horses have a bacterially dominated gut microbiota, that produces short chain fatty acids and lactate through anaerobic fermentation of structural carbohydrates [5]. Its main phyla are Firmicutes and Bacteroidetes [6] but there is a high variability, influenced by factors like ration [7], age [8][9][10], hindgut section [11], health status [12] and individual variation [13].…”
Section: Plos Onementioning
confidence: 99%